Association of Thrombocytopenia and Mortality in Critically ill Children Admitted to PICU in Tertiary Hospital In Biratnagar - Sah, Vijay Kumar; Giri, Arun; KC, Milan; Niraula, Niraj (Birat Journal of Health Sciences, 2019)
Introduction: Thrombocytopenia is a clinical condition characterized by decrease in number of platelets below the normal range. It is associated with bleeding tendency, hemodynamic instability, impaired inflammatory process and thus affecting host defence mechanism. There has been only few studies published till date in pediatric intensive care units suggesting thrombocytopenia is associated with increased mortality. Objectives: To determine the prevalence of thrombocytopenia in the critically ill children and its relationship with mortality in Pediatric intensive care unit (PICU) admitted children. Methodology: A prospective observational study was performed over a period of 12 months on 102 critically ill children admitted in PICU who fulfilled the criteria. Two patients left the study due to financial problems and as outcome could not be assessed on them, they were excluded from the study. Platelet count was noted at the time of admission and consecutively for the initial four days at PICU. Thrombocytopenia was defined as platelet count less than 150/nL. Mortality in PICU was recorded as primary outcome. Results: The prevalence of thrombocytopenia during consecutive 4 days was 34% (n=34) and at the time of admission in PICU was 16% (n=16) among 100 children analysed in the study. The mortality in the PICU was 27% (n=27). Mortality among thrombocytopenic children was 61.7% (n=21) as compared to 7.6% (n=5) in non-thrombocytopenic children (p=<0.001). Mortality was 18 times more for those who were thrombocytopenic at the time of admission as compared to those who subsequently developed thrombocytopenia during course of stay in PICU. Conclusion: Thrombocytopenia has significant association with increased mortality. Thrombocytopenic children at the time of admission have more likelihood of mortality than nonthrombocytopenic children in intensive care units.